‘No recuerdo que en el colegio me hablaran sobre pluralidad lingüística’. Un estudio cualitativo sobre las actitudes hacia la lengua minorizada de los maestros altoaragoneses en formación - Campos, I.O. (2019)
INTRODUCTION. Aragonese is one of the regional languages of the Spanish autonomous community of Aragon. In spite of its introduction as a school subject two decades ago, there are still few studies focused on its position in education. Considering the influence of teachers on the pupils’ linguistic attitudes, and their major role in decision-making about the presence of Aragonese in schools, it seems necessary to examine the attitudes of future teachers towards this language and its teaching. METHOD. With this aim, qualitative research was conducted among teacher education students on the Huesca campus of the University of Zaragoza. RESULTS. The data reveal that the majority of attitudes towards Aragonese are favourable or neutral attitudes. Nevertheless, the plurilingual reality of Aragon is still invisibilized in this autonomous community’s schools. Furthermore, the majority of future teachers consider that Aragonese should be taught as a subject and this attitude does not help the language to progress from its current situation. DISCUSSION. Considering that the contact with Aragonese or other regional languages is the main factor associated with committed attitudes towards its teaching among future teachers, we cannot be optimistic about its future in the school system.